Transitioning from Silence to Confidence: A Study of Non-Native English-Speaking Students in Higher Education - Simanjuntak, Christo Putra; Simanjuntak, Deborah Chaterin (Journal of English Language and Education, 2025)
This study explores the transformation of students from silent to confident English speakers, aiming to understand the underlying factors that contribute to this change. Many English learners struggle with speaking due to a combination of psychological, linguistic, and environmental challenges. This research investigates the reasons behind students’ initial shyness in speaking English, the specific difficulties they encounter—such as limited vocabulary, grammatical issues, and stage fright—and how they manage to overcome these barriers. It also examines the tension between maintaining native language proficiency while acquiring English fluency. The study was conducted using qualitative methods, with data collected through online interviews via Google Meet. Findings indicate that students develop confidence and fluency by adopting strategies tailored to their personal interests and social contexts, including listening to music, watching videos, and practicing with peers. These insights contribute to a deeper understanding of learner agency in language development and provide practical implications for English language education.